PEMBERDAYAAN KEWIRAUSAHAAN SANTRI PADA PESANTREN YANBU'UL QUR'AN KUDUS (EDUKASIA, 2019)
Entrepreneurship empowerment in pesantren is expected to have a positive impact, especially for santri or student. Empowerment is meaningful as an effort made by the Yanbu'ul Qur'an Islamic Boarding School Arwaniyah Foundation in introducing, fostering and developing the values of santri entrepreneurship and increasing students' interest in entrepreneurship. Entrepreneurship activities conducted are expected to foster the entrepreneurial character possessed by students. Entrepreneurial character is manifested in independence and leadership. With independence and leadership, students are expected to become role models for the surrounding community. Exemplary not only because they are graduates of Islamic boarding schools that are synonymous with da'wah activities, but also exemplary in economic activities by pocketing the entrepreneurial provision they have. Another goal with the provision of entrepreneurship is to improve the life skills of students. With the life skills that are owned, santri are felt ready when they enter the workforce later. Students are expected not only to depend on certain institutions to get jobs, but also can open their own jobs. By opening their own jobs, it will certainly open employment opportunities. This certainly can absorb unemployment in the community.